2020
DOI: 10.1109/access.2020.2995938
|View full text |Cite
|
Sign up to set email alerts
|

The Narrowband Internet of Things (NB-IoT) Resources Management Performance State of Art, Challenges, and Opportunities

Abstract: The Narrowband Internet of Things (NB-IoT) has been introduced in the 3rd Generation Partnership Project (3GPP) Rel-13 with the aim to provide low-cost, low-power, wide-area cellular connectivity for the Internet of Things. With the exponentially increasing number of connected wireless devices in the order of 100 billion, it has become crucial that researchers develop efficient resource management techniques to meet the 5 th Generation (5G) quality of service (QoS) requirements. Recently, several research chal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(41 citation statements)
references
References 76 publications
0
30
0
Order By: Relevance
“…We may assume t delay = 100µs as an average for a typical room condition with microseconds range delay is employed. The resulting throughput of the proposed random number generation for this case is then found to be f rng ≈ 5.4Kbps which is suitable for most low-cost, low-power embedded system applications with low data rate [42]. Due to the relatively slow throughput of the system, the generation of moderately large files sizes (>10MB) requires a long duration.…”
Section: Limitations Of the Proposed Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…We may assume t delay = 100µs as an average for a typical room condition with microseconds range delay is employed. The resulting throughput of the proposed random number generation for this case is then found to be f rng ≈ 5.4Kbps which is suitable for most low-cost, low-power embedded system applications with low data rate [42]. Due to the relatively slow throughput of the system, the generation of moderately large files sizes (>10MB) requires a long duration.…”
Section: Limitations Of the Proposed Methodsmentioning
confidence: 96%
“…However, for the target of this work, low data rate applications, the required data size is much lower. For instance, for a smart air monitoring system, the air quality index measurements are taken and transmitted in 5 to 15 minutes intervals where the data is 1 Byte long [42][43][44]. Hence, for one year, the monitoring system only sends 34.2KB to 102.6KB of data.…”
Section: Limitations Of the Proposed Methodsmentioning
confidence: 99%
“…Analyzing the research from the last three years, where important developments essentially on data speed, energetic efficiency, and scalability improvement have been proposed [28], it can be identified that several of these technologies can be precisely applied to micro perception measurements on toxins and pollutant agents, sensorial wave measurements, and fungi, bacteria and allergens detection.…”
Section: B Integrating Bioconstructions With Iotmentioning
confidence: 99%
“…Resource management & Scheduling [25]- [27] V Synchronization [28]- [37] III.A Uplink demodulation [38]- [47] IV.A & IV.B Downlink demodulation [48]- [53] IV.B Energy Saving [54]- [57] V.H & VI.B Positioning [58]- [60] VI.A Challenges & perspectives [17], [20]- [22], [61]- [64] I Release 13 [65]- [77] I to V 3GPP references Release 14 [78]- [85] VI.A Release 15 [86]- [92] I & VI.B…”
Section: Topicsmentioning
confidence: 99%
“…Others focus on specific functionality like power consumption [54], random access [18], [19], resource management [25], scheduling issues, and solutions for uplink or downlink physical channels [26], [27]. Many others provide surveys on NB-IoT technology to offer a complete summary on system capabilities, constraints, and challenges [20]- [22], [64]. In particular, the authors of [62] provide a detailed overview of the open issues and pending challenges related to NB-IoT.…”
Section: B State Of the Artmentioning
confidence: 99%